PENGEMBANGAN BUKU AJAR EKOLOGI TUMBUHAN BERBASIS PENELITIAN KEANEKARAGAMAN VEGETASI HUTAN LINDUNG SUMBER UBALAN - Chitra Dewi Yulia Christie; Nia Agus Lestari; Hasbi Ashshiddiqi W.K; Indah Dwi Lestari (LPPM Universitas Kahuripan Kediri, 2022)
Biodiversity in Indonesia is high and very diverse, so it is important to conduct research on it, and no less important is the development of research-based textbooks so that textbooks can be more contextual. Research textbooks on plant biodiversity have not yet been developed specifically, so it is necessary to develop textbooks on agricultural ecology courses which are one of the courses that must be taken by undergraduate students of the Agrotechnology study program, Kahuripan University, Kediri. The method used in this study adapts Borg and Gall's Research and Development (R&D) development method. The test results obtained from the media expert validator are 88% and from the material expert validator 90% then from the product trial is 87%